Dynamics of violence disclosure among women in Kenya: trends, changes and associated factors - Joshua Okyere; Abigail Kabukie Dosoo; Castro Ayebeng; Kwamena Sekyi Dickson (BMC, 2024)
Abstract Background Kenya has ratified and enacted several frameworks and laws in a bid to reduce the incidence of IPV and improve disclosure of violence experience. With these legal and structural mechanisms in place, women's disclosure of IPV is expected to show a positive trend over the years. We examined the trends and factors associated with disclosure of IPV among women in Kenya. Methods The 2008, 2014 and 2022 Kenya demographic and health survey data was used, with a weighted sample of 6,093 women aged 15-49 years. The sample size for 2008, 2014 and 2022 were 1350, 1165, and 3578, respectively. Violence disclosure was the outcome variable. A logistic regression model was fitted to estimate the predicted probabilities (margins) of reporting violence for each year. Additionally, a multivariable logistic regression was performed to assess factors associated with violence disclosure using a backward stepwise approach. Results We found a statistically significant increase in the odds of disclosing violence by 65% from 2008 to 2022 [OR = 1.65; 95%CI: 1.41-1.94, p < 0.001]. The odds of disclosing violence increased significantly by 35% from 2008 to 2014 (OR = 1.35, p = 0.003), and further declined by 23% from 2014 to 2022 (OR = 1.23, p = 0.012). Violence disclosure significantly increased with age. Women in the richest wealth index (AOR = 1.78, 95% CI: 1.46-2.16), those currently working (AOR = 1.23, 95% CI: 1.08-1.41), had witnessed parental violence (AOR = 1.14, 95% CI: 1.01-1.29), or had partners who drank alcohol (AOR = 1.41, 95% CI: 1.24-1.59) were also more likely to disclose violence. Conclusion The findings from this study indicate that violence disclosure among women in Kenya has significantly increased over the years. Women in higher wealth quintile, currently employed, and those exposed to violence in their parental homes were more likely to disclose violence, highlighting the importance of economic empowerment and addressing intergenerational transmission of violence in increasing disclosure rates.